Anti‐factor IXa/X bispecific antibody (ACE910): hemostatic potency against ongoing bleeds in a hemophilia A model and the possibility of routine supplementation. (February 2014) - Muto, A.; Yoshihashi, K.; Takeda, M.; Kitazawa, T.; Soeda, T.; Igawa, T.; Sakamoto, Y.; Haraya, K.; Kawabe, Y.; Shima, M.; Yoshioka, A.; Hattori, K.
Summary Background We previously reported that a humanized anti‐factor IXa/X bispecific antibody, hBS23, mimics the function of FVIII even in the presence of FVIII inhibitors, and has preventive hemostatic activity against bleeding in an animal model of acquired hemophilia A. After further molecular engineering of hBS23, we recently identified an improved humanized bispecific antibody, ACE910, for clinical investigation. Objectives To elucidate the in vivo hemostatic potency of ACE910 by examining its effect against ongoing bleeds, and to determine its pharmacokinetic parameters for discussion of its potency for prophylactic use. Methods A non‐human primate model of acquired hemophilia A was established by injecting anti‐primate FVIII neutralizing antibody. When bleeds emerged following an artificial bleed‐inducing procedure, either ACE910 or recombinant porcine FVIII (rpoFVIII) was intravenously administered. rpoFVIII was additionally administered twice daily on the following 2 days. Bleeding symptoms were monitored for 3 days. A pharmacokinetic study and multiple‐dosing simulations of ACE910 were also performed. Results A single bolus of 1 or 3 mg kg−1 ACE910 showed hemostatic activity comparable to that of 10 U kg−1 (twice daily) rpoFVIII against ongoing bleeds. The determined ACE910 pharmacokinetic parameters included a long half‐life (3 weeks) and high subcutaneous bioavailability (nearly 100%). The simulation results based on pharmacokinetic parameters indicated that the above hemostatic level could be maintained with once‐weekly subcutaneous administration of ACE910, suggesting the possibility of more effective prophylaxis. Conclusions ACE910 may offer an alternative on‐demand treatment option for patients with hemophilia A, as well as user‐friendly and aggressive routine supplementation.